Gut microbiota: A novel and potential target for radioimmunotherapy in colorectal cancer - Yuan, Hanghang; Gui, Ruirui; Wang, Zhicheng; Fang, Fang; Zhao, Hongguang (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is one of the most common cancers, with a high mortality rate, and is a major burden on human health worldwide. Gut microbiota regulate human immunity and metabolism through producing numerous metabolites, which act as signaling molecules and substrates for metabolic reactions in various biological processes. The importance of host-gut microbiota interactions in immunometabolic mechanisms in CRC is increasingly recognized, and interest in modulating the microbiota to improve patient’s response to therapy has been raising. However, the specific mechanisms by which gut microbiota interact with immunotherapy and radiotherapy remain incongruent. Here we review recent advances and discuss the feasibility of gut microbiota as a regulatory target to enhance the immunogenicity of CRC, improve the radiosensitivity of colorectal tumor cells and ameliorate complications such as radiotoxicity. Currently, great breakthroughs in the treatment of non-small cell lung cancer and others have been achieved by radioimmunotherapy, but radioimmunotherapy alone has not been effective in CRC patients. By summarizing the recent preclinical and clinical evidence and considering regulatory roles played by microflora in the gut, such as anti-tumor immunity, we discuss the potential of targeting gut microbiota to enhance the efficacy of radioimmunotherapy in CRC and expect this review can provide references and fresh ideas for the clinical application of this novel strategy.